2020
DOI: 10.1029/2020tc006116
|View full text |Cite
|
Sign up to set email alerts
|

Active Extension in a Foreland Trapped Between Two Contractional Chains: The South Apulia Fault System (SAFS)

Abstract: The response of continental forelands to subduction and collision is a widely investigated topic in geodynamics. The deformation occurring within a foreland shared by two opposite‐verging chains, however, is uncommon and poorly understood. The Apulia Swell in the southern end of the Adria microplate (Africa‐Europe plate boundary, central Mediterranean Sea) represents one of these cases, as it is the common foreland of the SW verging Albanides‐Hellenides and the NE verging Southern Apennines merging into the SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…eu/ AHEAD) databases, also supported by additional considerations by Argnani et al (2001), in the Otranto channel, where some small magnitude events were located instrumentally (D'Ingeo et al 1980;Gasparini et al 1985;Favali et al 1990). As we are not able to model a 3D geometry for this source, we represented it as a horizontal 20-km deep polygon, whose top does not intersect the surface, in agreement with the Argnani et al (2001) interpretation confirmed also by the recent data and interpretation of Maesano et al (2020). This geometry could also justify the wide perceptibility area of the 1743 earthquake.…”
Section: The Fault Modelsupporting
confidence: 79%
See 1 more Smart Citation
“…eu/ AHEAD) databases, also supported by additional considerations by Argnani et al (2001), in the Otranto channel, where some small magnitude events were located instrumentally (D'Ingeo et al 1980;Gasparini et al 1985;Favali et al 1990). As we are not able to model a 3D geometry for this source, we represented it as a horizontal 20-km deep polygon, whose top does not intersect the surface, in agreement with the Argnani et al (2001) interpretation confirmed also by the recent data and interpretation of Maesano et al (2020). This geometry could also justify the wide perceptibility area of the 1743 earthquake.…”
Section: The Fault Modelsupporting
confidence: 79%
“…The epicentre of this event is quite uncertain, and its location reported in Italian [offshore the Salento peninsula (Rovida et al 2011)] and Greek [south of Corfu island (Papazachos and Papazachou 2003)] catalogues differ notably. Although different faults have been proposed for this earthquake (Argnani et al 2001;Galli and Naso 2008;Milia et al 2017;Maesano et al 2020), the source remains poorly constrained: we considered the source proposed in the DISS (Basili et al 2008) and the AHEAD (European Archive of Historical Earthquake Data, www. emidi us.…”
Section: The Fault Modelmentioning
confidence: 99%
“…Slip rate is a derived quantity that bears the epistemic uncertainty of both variables needed to calculate them: the amount of slip and the age of the reference horizon. To this end, we adopted the probabilistic approach for the slip rate calculation and reporting proposed by Zechar and Frankel (2009), which has been already applied in different tectonic contexts, continental and offshore faults, as well as at different spatial and temporal scales (Frankel et al, 2011;Gold and Cowgill, 2011;Chevalier et al, 2012;Maesano et al, 2020).…”
Section: Probabilistic Slip Rate Assessmentmentioning
confidence: 99%
“…The different approaches to slip rate calculation and the variability of the results can be treated considering all the uncertainties involved and providing a probabilistic approach to the results (Zechar and Frankel, 2009;Styron, 2019). The determination of slip rates of blind faults is mostly based on the analysis of deformed syn-tectonic markers either on surface exposures (Ward and Valensise, 1996;Vannoli et al, 2004;Gunderson et al, 2013Gunderson et al, , 2018Livio et al, 2014;Tiberti et al, 2014) or in the subsurface (Dolan et al, 2003;Wang et al, 2014;Maesano et al, 2015Maesano et al, , 2020Bergen et al, 2017), and requires a good three-dimensional geometrical definition of the underlying fault (Shaw et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Ms, Marisa well; Mr, Marta well. Transform Edge Propagator (STEP, also called tear) faults occur (Gallais et al, 2013;Orecchio et al, 2014;Gutscher et al, 2016;Maesano et al, 2020). STEP faults produce tearing in the slab and generally propagate perpendicular to the subduction strike (Nijholt and Govers, 2015).…”
Section: Geological Setting Se Tyrrhenian Basin and The Adjacent Calabrian Arcmentioning
confidence: 99%